PERSEPSI IBU RUMAH TANGGA TERHADAP PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM BERDASARKANPENDIDIKAN DAN USIA DI DESA TAUGI KECAMATAN MASAMA KABUPATEN BANGGAI - ABDUL MUIN KENTA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2017)
AbstractThis study aimed to describe the perception of housewives to the use of an intrauterine device (IUD). The method used in this research is descriptive method. Population and sample are housewives who use an IUD in the village Taugi Masama District of Banggai that totaled 15 people. Data collection techniques obtained through a questionnaire to be further analyzed using the percentage calculation. The results showed that the perception of housewives against IUD Based on education and age in the village Taugi generally included in the category enough with the percentage of 44.99%. This shows that the perception of housewives against IUD use by education and age in the village Taugi not been successful in use, due to economic factors and low education levels housewife, reaching 51.99%.Keywords : Perception, intrauterine device